TRANSFORMATION OF KYRGYZ NATIONALISM IN RUSSIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
With the beginning of the invasion of the Russian Empire, the process of radical transformation of cultural space began in the region, transformations affected the civilizational foundations of the existence of the peoples of Central Asia. The transition from an ethnic state to a nation. About the natural reaction of humanists to the rapidly and unpredictably changing reality, where the usual and understandable order of things disappeared.
Keywords: transformation, pre-Soviet period, nomadic world, settlement, Kokand Khanate, zamanists, nationalism, culture, civilization